1981
DOI: 10.1126/science.7221552
|View full text |Cite
|
Sign up to set email alerts
|

Hibernation and Longevity in the Turkish Hamster Mesocricetus brandti

Abstract: A positive correlation was found between the length of life of 288 Turkish hamsters and the amount of time spent in hibernation, suggesting that the process of aging is slowed during hibernation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(84 citation statements)
references
References 7 publications
2
79
0
1
Order By: Relevance
“…Hamsters conserve energy during winter by hibernating and reducing their body temperatures. Lyman (1981) observed that if Turkish hamsters Mesocricetus brandti in the laboratory were prevented from hibernating then their increased energy expenditure and increased body temperatures were associated with a decrease in their lifespan.…”
Section: (Iii) Environmental Factorsmentioning
confidence: 99%
“…Hamsters conserve energy during winter by hibernating and reducing their body temperatures. Lyman (1981) observed that if Turkish hamsters Mesocricetus brandti in the laboratory were prevented from hibernating then their increased energy expenditure and increased body temperatures were associated with a decrease in their lifespan.…”
Section: (Iii) Environmental Factorsmentioning
confidence: 99%
“…The reduction of body temperature in CR rodents is similar to the torpor observed in hibernating animals. Studies in both hamsters and reptiles (39,40) have demonstrated a positive relationship between time spent hibernating and life span.…”
Section: Bioenergeticsmentioning
confidence: 99%
“…This suggests that a hibernation-specific mechanism is not required to explain the slower ageing of small hibernating mammals. Despite this, a small number of studies have found strong correlations between the use of daily torpor or hibernation and indices of rate of ageing [6][7][8], suggesting that torpor expression by endothermic animals might have a physiological effect on rates of ageing [9].…”
Section: Introductionmentioning
confidence: 99%